Patterns of emergency department utilization for LVAD patients compared with non-LVAD patients. (October 2020) - Al-Ani, Mohammad; Gul, Sarah S.; Khatri, Abhishek; Chowdhury, Muhammad Abdul Baker; Drabin, Matthew; Murphy, Travis; Allen, Brandon; Aranda, Juan M.; Vilaro, Juan; Jeng, Eric I.; Arnaoutakis, George J.; Parker, Alex M.; et al.
Abstract: Background: Left ventricular assist device (LVAD) patients are vulnerable to over-utilization of resources. Methods and results: We explored the pattern of emergency department (ED) presentations of LVAD patients and their costs compared with non-LVAD heart failure patients. ED visits between 7/2008 and 7/2017 were reviewed to identify 145 LVAD patients, and 435 patients with known heart failure were selected using propensity score matching for age and sex. ED evaluation metrics, hospitalization cost, and length of stay (LOS) were analyzed. Although the most common ED presentations and their frequency differed between groups, few were LVAD specific. LVAD patients were more likely to have taken personal vehicles or be flown to the ED. They had similar times to triage, rooming, and physician evaluation compared with non-LVAD patients. However, LVAD patients were noted to have a shorter time from physician assessment to disposition (109.8 min vs. 177.0 min, p < 0.001) and, overall, LVAD patients had shorter ED LOS (6.33 vs. 9.82 hrs, p = 0.0001). For patients admitted, no significant difference was found between groups in hospital LOS (6.67 vs 6.58 days, p = 0.928) or total cost (28, 766 vs 21, 524, p = 0.087). Conclusion: Shorter disposition times without increases in LOS or costs may identify a created healthcare disparity among LVAD patients.